Strategic targeting of agricultural conservation easements as a growth management tool - Stoms, D. M.; Jantz, P. A.; Davis, F. W.; DeAngelo, G. (Land Use Policy, 2009)
Public and private programs have preserved an estimated 730,000 ha of agricultural land in the United States, by acquiring agricultural conservation easements (ACEs) that retire a property's development rights. ACEs could be a potent tool for smart growth if strategically targeted. This paper attempts to quantify measures of strategic farmland preservation as guidance for planners. Evaluating the placement of 318 ACEs in the San Francisco Bay of California produced mixed results. Preservation and development of agricultural land were both in conformance with general plans. In contrast, we found little evidence of ACEs being used on a regional scale to reinforce urban growth boundaries. Recently ACEs have begun to coalesce into larger blocks of preserved agricultural land, but not near the rural-urban fringe. We encourage planners to consider farmland preservation as a politically-acceptable tool to complement traditional planning tools to minimize low-density sprawl.
Keywords: strategic conservation planning spatial targeting GIS smart growth farmland preservation urban growth boundaries